2009
DOI: 10.1093/bmb/ldp042
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and environmental factors in primary angle-closure glaucoma

Abstract: Whenever in doubt, patients at risk of PACG who are starting on drug therapy known to provoke angle closure or aggravate the condition should be referred for detailed gonioscopic examination of the anterior chamber by an ophthalmologist. AREAS FOR DEVELOPING RESEARCH: The use of new imaging methods such as anterior segment optical coherence tomography to assess the presence or risk of angle closure is gaining popularity, and may offer a more rapid method of identifying people who are at risk of sight loss from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…This may increase the likelihood of a mydriaticinduced acute ACG attack due to pupillary dilation and a subsequent spike in IOP. 121 Yet, to date it is unknown whether these environmental factors are more significant in patients with certain genetic predispositions.…”
Section: Nebmentioning
confidence: 99%
“…This may increase the likelihood of a mydriaticinduced acute ACG attack due to pupillary dilation and a subsequent spike in IOP. 121 Yet, to date it is unknown whether these environmental factors are more significant in patients with certain genetic predispositions.…”
Section: Nebmentioning
confidence: 99%
“…Iatrogenic glaucoma can occur secondary to drug administration and can result in blindness due to optic nerve damage caused by increased IOP [9]. Adrenergic agents, anticholinergics, antihistamines, and antidepressants are known to cause acute closed-angle glaucoma [10,11]. Steroids can also increase the incidence of glaucoma [9,12].…”
Section: Discussionmentioning
confidence: 99%
“… Medications Medications such as Antidepressants, major classes of antidepressants that cause angle closure are tricyclic antidepressants (TCAs) and serotonin-specific reuptake inhibitors (SSRIs). It has been suggested that nebulized administration of bronchodilator medications either α2-adrenergic agonists or anticholinergic medications for Asthma and chronic obstructive airway disease allows a significant dose to be absorbed over the conjunctiva and cornea.The British National Formulary lists 'glaucoma' as a contraindication to use of anticholinergic for urinary incontinence and as antispasmodics, although it makes no distinction between open-angle glaucoma and angle-closure glaucoma, nor between patients who have had previous laser treatment for their occludable anterior chamber angles.There have been several case series of patients suffering AAC (acute angle closure) after general anesthesia and have resulted in permanent visual loss from glaucomatous optic neuropathy.Many over-the-counter cold and cough remedies contain constituents, included as antihistamines or decongestants, which also have marked sympathomimetic or anticholinergic effects [18].…”
Section:  Diabetesmentioning
confidence: 99%